Multiple Intelligences in Prospective Biology Teachers and Their Role in Self-Awareness and Learning Strategies - Nanda Eska Anugrah Nasution (Journal of Pedagogical and Teacher Professional Development, 2025)
This study explores the multiple intelligences of prospective teachers and their role in self-awareness and learning strategies, with a focus on second-year students in the Biology Education program at UIN Kiai Haji Achmad Siddiq Jember. Using a qualitative descriptive research design, the study gathered data from 44 voluntarily participating students through multiple intelligence assessments, self-reflection questionnaires, semi-structured interviews, and Focus Group Discussions. The findings reveal that the most dominant intelligence type among respondents was intrapersonal intelligence (25%, n=11), followed by naturalistic intelligence (20.5%, n=9), and then musical intelligence (18.2%, n=8). This was followed by four intelligence types with the same percentage (6.8%, n=3), namely bodily-kinesthetic intelligence, spatial-visual intelligence, interpersonal intelligence, and logical-mathematical intelligence. Lastly, two intelligence types had the same number of respondents (4.5%, n=2), namely existential intelligence and linguistic intelligence. Students with high intrapersonal intelligence exhibited strong self-reflection and independent learning tendencies, while those with naturalistic intelligence preferred experiential, nature-based learning. This study highlights the importance of self-awareness in optimizing learning strategies and suggests that teacher education programs incorporate multiple intelligence-based approaches to support diverse learning styles.